Ultrasonic fatigue testing device under biaxial bending (Fracture and Structural Integrity, 2016)
A new fatigue testing device has been developed to test specimens under biaxial loading at 20 kHz. A flat smooth specimen with a disc geometry is placed on a torus frame and cyclically loaded at the center of its upper face. Disc bending generates a biaxial proportional stress state at the center of the lower face. Any positive loading ratio can be applied. A cast aluminum alloy (used to produce cylinder heads) has been tested under biaxial bending using this device in order to determine its fatigue strength at 109 cycles under high hydrostatic pressure. Self-heating is moderate but macroscopic fatigue cracks after testing are very long. First results in VHCF regime are consistent with literature results obtained under similar stress state but in HCF regime and at 20 Hz.
Keywords: Gigacycle fatigue; Biaxial loading; Bending; Cast aluminum alloy; Ultrasonic testing machine